Strategy for Developing Arabica Coffee Agroindustry in Badung Regency to Enhance Regional Competitiveness - Maria Mahdalena Yulia Ratnaningtyas; Yohanes Parlindungan Situmeang; I Gusti Bagus Udayana; Ida Bagus Komang Mahardika; I Gede Pasek Mangku; I Gusti Agus Maha Putra Sanjaya; N.K.D.A Dewi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Coffee is a vital plantation commodity for the Indonesian economy, yet the potential of Arabica coffee in Petang District, Badung Regency, remains underutilized due to a reliance on raw material sales that yield low added value. This study analyzes the current state of the Arabica coffee agroindustry and identifies internal and external factors to inform sustainable development strategies. Utilizing a mixed-methods approach with SWOT analysis and IFE/EFE matrices, data were collected through interviews, observations, and stakeholder questionnaires. The findings reveal that while the industry benefits from high product quality and ideal agroclimatic conditions, it is hindered by limited processing technology, restricted capital access, and weak branding. Consequently, the recommended strategies focus on enhancing post-harvest quality, strengthening farmer institutions, diversifying processed products, and integrating tourism-based marketing to boost the competitiveness and added value of Badung Regency’s Arabica coffee Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate Action